Development and Scaling of Sustainable Feeds for Resilient Aquatic Food Systems in Sub-Saharan Africa: Climate change and environmental analysis - Mubaya, Chipo; Ndebele-Murisa, Mzime; Kapute, Fanuel; Samundengo, Angela; Yossa, Rodrigue (WorldFish, 2023)
This study used a landscape approach to investigate the climate and environment and the links between current fish feed ingredients and their potential as novel sources of fish feed in the three project countries of Kenya, Nigeria and Zambia. The objective was to analyze the climate and environment in relation to local ingredients and current feeds and to identify opportunities for FASA to harness the environment within the novel fish feed landscape and prevailing climatic and environmental conditions in Kenya, Nigeria and Zambia. This report, therefore, provides a situational analysis of the natural, physical and social aspects of the climate and environment and how this bears on ingredients for fish feeds within the locations of the study countries. It will also feed into the life cycle assessment (LCA) report for fish feeds for the same study areas and, consequently, the country outcomes report that will identify risks for the project. More specifically, this report contributes to FASA’s outcome of developing and scaling sustainable feeds for resilient food systems in Sub-Saharan Africa to help identify strategies and opportunities that increase environmental sustainability and climate resilience in the fish feed landscape in Kenya, Nigeria and Zambia. For this study, we used a mixed research design approach that embraced both quantitative and qualitative methods in a climate and environmental analysis and in relation to fish feeds. This involved doing a literature review, engaging with fish farmers, fish feed producers and other stakeholders, and using participatory processes to collect data.